Higher Total Protein Intake and Change in Total Protein Intake Affect Body Composition but Not Metabolic Syndrome Indexes in Middle-Aged Overweight and Obese Adults Who Perform Resistance and Aerobic Exercise for 36 Weeks(1)(2)(3) - Campbell, Wayne W (J Nutr, 2015)
Background: Studies assessing the effects of protein supplementation on changes in body composition (BC) and health rarely consider the impact of total protein intake (TPro) or the change in TPro (CTPro) from participants’ usual diets. Objective: This secondary data analysis assessed the impact of TPro and CTPro on changes in BC and metabolic syndrome (MetS) indexes in overweight and obese middle-aged adults who participated in an exercise training program. Methods: Men and women [n = 117; age: 50 ± 0.7 y, body mass index (BMI; in kg/m(2)): 30.1 ± 0.3; means ± SEs] performed resistance exercise 2 d/wk and aerobic exercise 1 d/wk and consumed an unrestricted diet along with 200-kcal supplements (0, 10, 20, or 30 g whey protein) twice daily for 36 wk. Protein intake was assessed via 4-d food records. Multiple linear regression model and stratified analysis were applied for data analyses. Results: Among all subjects, TPro and CTPro were inversely associated (P < 0.05) with changes in body mass, fat mass (FM), and BMI. Changes in BC were different (P < 0.05) among groups that consumed <1.0 (n = 43) vs. ≥1.0 to <1.2 (n = 29) vs. ≥1.2 g · kg(−1) · d(−1) (n = 45). The TPro group with ≥1.0 to <1.2 g · kg(−1) · d(−1) reduced FM and %FM and increased percentage of LM (%LM) compared with the lowest TPro group, whereas the TPro group with ≥1.2 g · kg(−1) · d(−1) presented intermediate responses on changes in FM, %FM, and %LM. The gain in LM was not different among groups. In addition, MetS indexes were not influenced by TPro and CTPro. Conclusions: In conjunction with exercise training, higher TPro promoted positive changes in BC but not in MetS indexes in overweight and obese middle-aged adults. Changes in TPro from before to during the intervention also influenced BC responses and should be considered in future research when different TPro is achieved via diet or supplements. This trial was registered at clinicaltrials.gov as NCT00812409.